PENINGKATAN PRODUKTIVITAS MELALUI UPAYA ENVIROMENTAL RISK ANALYSIS UNTUK MENDUKUNG PELAKSANAAN GREEN PRODUCTIVITY - Agus Supriyadi; Athika Sidhi Cahyana (Universitas Ahmad Dahlan Indonesia, 2019)
PG XYZ as one of the sugar industries that have the potential for waste pollution needs to make improvements both in the production process and in the management of its environment. With various existing waste conditions such as in industrial wastewater. Therefore, a systematic application is needed to minimize the possibility of environmental risks. so that identification, assessment and analysis of environmental risk based on the concept of environmental risk management using qualitative methods, semi-quantitative methods and the significance of aspects. followed by EPI calculation to support the implementation of green productivity. the objectives of this study are to identify and analyze environmental risks in the sugar processing industry wastewater based on the concept of environmental risk management. Evaluate the factors that influence the productivity of environmental performance to support the implementation of green productivity. The result of this study is that installation of wastewater treatment has a low risk with a total risk value of 77 which means that management is carried out by routine procedures. Whereas the results of the environmental risk assessment of production activities which have the most environmental impact are turbine oil lubrication at the boiler station with a score of 1701, at the